2023
DOI: 10.1038/s41598-023-31598-5
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 expression is increased in human first trimester placenta from pregnant women classified as overweight or obese

Abstract: Obesity has become a global health challenge also affecting reproductive health. In pregnant women, obesity increases the risk of complications such as preterm birth, macrosomia, gestational diabetes, and preeclampsia. Moreover, obesity is associated with long-term adverse effects for the offspring, including increased risk of cardiovascular and metabolic diseases and neurodevelopmental difficulties. The underlying mechanisms are far from understood, but placental function is essential for pregnancy outcome. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Placental p-glycoprotein has been shown to decline through pregnancy (Sun et al, 2006) which might cause some variation in the studies identified. There are also reports that p-glycoprotein is affected by obesity (Justesen et al, 2023;Wang et al, 2015). Furthermore, the use or consumption of several drugs may also influence the CYP3A4 metabolising capacity (Abduljalil et al, 2020;Langhammer & Nilsen, 2014) which is a circumstance that was not taken into account in the investigated studies in this systematic review.…”
Section: Discussionmentioning
confidence: 98%
“…Placental p-glycoprotein has been shown to decline through pregnancy (Sun et al, 2006) which might cause some variation in the studies identified. There are also reports that p-glycoprotein is affected by obesity (Justesen et al, 2023;Wang et al, 2015). Furthermore, the use or consumption of several drugs may also influence the CYP3A4 metabolising capacity (Abduljalil et al, 2020;Langhammer & Nilsen, 2014) which is a circumstance that was not taken into account in the investigated studies in this systematic review.…”
Section: Discussionmentioning
confidence: 98%